Pengaruh Gaya Kepemimpinan Berorientasi Prestasi dan Motivasi Terhadap Kinerja Karyawan dengan Disiplin Kerja Sebagai Variabel Intervening pada PT. Bank Syariah Indonesia KCP Medan Petisah - Silaen, Lena Mardiana; Imsar; Syahriza, Rahmi (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
This study analyzes the influence of achievement-oriented leadership style and motivation on employee performance, with work discipline as an intervening variable, conducted at Bank Syariah Indonesia KCP Medan Petisah. The data collection method used is quantitative research with primary data obtained from questionnaires. The population of the study is all employees of Bank Syariah Indonesia KCP Medan Petisah. The sample was taken using saturated sampling with a total of 22 employees. The results of the study show that, partially, achievement-oriented leadership style and motivation have an insignificant influence on performance, while motivation and work discipline have a positive and significant impact on performance. Motivation also has a significant influence on work discipline. Meanwhile, employee performance has a positive influence on work discipline. From the explanation of the research results, the variables of achievement-oriented leadership style, motivation, employee performance, and work discipline all have a positive influence on Bank Syariah Indonesia KCP Medan Petisah.